Legal Protection of Students Who Are Victims of Abuse of Educators in Asahan District in Terms of Law No. 35 of 2014 Concerning Child Protection - Yani Zandroto; Hafsah Hafsah; Hasan Matsum (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2020)
This study examines the violence of educators against their students that occurred in the Asahan District. This case is interesting to study because educators should not perpetrate violence against their students, and students should receive guaranteed protection from such acts of violence. The focus of the problems studied is: 1) forms of legal protection provided by Law No. 35 of 2014 for students, and 2) the role of the government, school supervisors and education staff in providing legal protection for students who experience acts of abuse by educators in the school environment. This type of research is qualitative with a juridical and normative approach. This study found that the role of the Asahan District Government in efforts to prevent acts of abuse and violence against students/children both within the school environment and outside the school environment is by establishing a Child-Friendly District (LKA) as a form of concern for child growth and development and safe and comfortable life For children. The role of the Asahan Regency Government in efforts to prevent acts of abuse and violence against students/children both within the school environment and outside the school environment is by establishing a Child-Friendly District (LKA) as a form of concern for child growth and development and safe and comfortable life for children. Legal protection for children that has been carried out, if based on Law No. 35 of 2014, more serious efforts are needed so that the realization of the values of the law can be realized properly.Penelitian ini mengkaji kekerasan para pendidik terhadap para siswanya yang terjadi di Kabupaten Asahan. Kasus ini menarik diteliti karena kekerasan tidak seharusnya dilakukan oleh pendidik terhadap peserta didiknya, dan peserta didik seharusnya mendapat jaminan perlindungan dari tindak kekerasan tersebut. Fokus permasalahan yang dikaji adalah: 1) bentuk-bentuk perlindungan hukum yang diberikan oleh Undang-Undang No 35 Tahun 2014 bagi peserta didik, dan 2) peran pemerintah, pengawas sekolah dan tenaga kependidikan dalam memberikan perlindungan hukum bagi peserta didik yang mengalami tindak penganiayaan oleh tenaga pendidik dilingkungan sekolah. Jenis penelitian ini adalah kualitatif dengan pendekatan yuridis dan normatif. Penelitian ini menemukan bahwa peranan Pemerintah Kabupaten Asahan dalam upaya pencegahan tindakan penganiayaan maupun kekerasan terhadap peserta didik/anak baik dilingkungan sekolah maupun diluar lingkungan sekolah yaitu dengan membentuk Kabupaten Layak Anak (LKA) sebagai wujud kepedulian terhadap tumbuh kembang anak dan keberlangsungan hidup yang aman dan nyaman bagi anak. Peranan Pemerintah Kabupaten Asahan dalam upaya pencegahan tindakan penganiayaan maupun kekerasan terhadap peserta didik/anak baik dilingkungan sekolah maupun diluar lingkungan sekolah yaitu dengan membentuk Kabupaten Layak Anak (LKA) sebagai wujud kepedulian terhadap tumbuh kembang anak dan keberlangsungan hidup yang aman dan nyaman bagi anak. Perlindungan hukum terhadap anak yang sudah dilakukan, jika berdasarkan UU No 35 tahun 2014, perlu upaya lebih serius agar perwujudan dari nilai-nilai UU tersebut dapat terealisasikan dengan baik.